A Critical Review of Studies Assessing Interpretation Bias Towards Social Stimuli in People With Eating Disorders and the Development and Pilot Testing of Novel Stimuli for a Cognitive Bias Modification Training - Rowlands, Katie; Wilson, Emma; Simic, Mima; Harrison, Amy; Cardi, Valentina (Frontiers in Psychology, 2020)
People with eating disorders display a negative interpretation bias towards ambiguous social stimuli. This bias may be particularly relevant to young people with the illness due to the developmental salience of social acceptance and rejection. The overall aim of this study was to systematically develop and validate stimuli for a cognitive bias modification training to reduce a social rejection-related negative interpretation bias in young people with eating disorders. A mixed-methods design was used to achieve this aim. A review of the literature was conducted using EMBASE, MEDLINE, PsycINFO, Web of Science, and PubMed. Six studies were included in the review. Focus groups were held with patients with eating disorders, carers and healthcare professionals. Content analysis was used to identify key themes from the qualitative data. Based on these themes, a total of 339 scenarios were generated by the researchers. Salient themes identified from the focus group data included virtual rejection/exclusion, rejection associated with an aspect of the eating disorder, rejection triggered by ambiguous/benign comments or behaviours of others and rejection perceived when confiding in others. Patients rated these scenarios in terms of their age-relevance and emotional salience and 301 scenarios were included in the final stimulus set. These materials may be used by researchers conducting future experimental research into the potential benefits of interpretation bias training for young people with eating disorders.